Multiband monopole antenna with minimised ground plane influence for portable devices. Issue 13 (6th September 2017) - Khan, Rizwan; Al‐Hadi, Azremi Abdullah; Soh, Ping Jack; Ali, Muhsin; Owais, Owais; Islam, Imtiaz
Abstract : A multiband monopole antenna with minimised ground plane influence for portable devices is presented. This antenna operates at LTE band 13 (0.746–0.787 GHz), GPS, LTE band 11 (1.427–1.495 GHz), LTE band 3 (1.71–1.88 GHz), WLAN (2.4–2.48 GHz) and WiMAX (3.3–3.88 GHz) with at least −6 dB of reflection coefficient. The performance of antennas for portable devices is commonly influenced by the ground plane to result in variation in terms of operating frequency, impedance bandwidth and radiation pattern. Via a parametric investigation of the antenna geometry and its integration with peripherals devices, it is validated that the influence of the ground plane is minimised by adjusting the feed position. This in turn reduces the current distribution on the ground plane. It is also noticed that the impedance matching level is also more robust with the reduction of ground plane influence. The antenna features an omnidirectional radiation pattern across the all operating frequencies. Fabrication and assessment of the fabricated antenna indicated a close agreement with simulations.